2018
DOI: 10.1097/mao.0000000000001924
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral and Bilateral Audiological Benefit With an Adhesively Attached, Noninvasive Bone Conduction Hearing System

Abstract: Both bone conduction devices seem to be a valid treatment for patients with conductive hearing loss and minor sensorineural hearing loss component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
2
30
0
1
Order By: Relevance
“…These sound field threshold measurements clearly demonstrate the benefit derived from ADHEAR in the aided condition when compared to the unaided measurements. The current results are fairly comparable to a previous study reporting a functional gain of 24.3 ± 5.2 dB HL using the ADHEAR system [Gawliczek et al, 2018]. In general, comparison of the current findings with previous reports on other bone conduction technologies may not be straightforward given the differences in methodologies.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These sound field threshold measurements clearly demonstrate the benefit derived from ADHEAR in the aided condition when compared to the unaided measurements. The current results are fairly comparable to a previous study reporting a functional gain of 24.3 ± 5.2 dB HL using the ADHEAR system [Gawliczek et al, 2018]. In general, comparison of the current findings with previous reports on other bone conduction technologies may not be straightforward given the differences in methodologies.…”
Section: Discussionsupporting
confidence: 78%
“…However, these speech recognition scores are lower than those reported for bone conduction hearing systems. For example, using ADHEAR [Gawliczek et al, 2018], a gain of 49% at 65 dB SPL was reported. However, that study was done on induced conductive hearing loss (normal-hearing persons) and not real patients like in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a significant number of patients chooses not to use or to discontinue the use of bone conduction devices because either a surgical intervention is needed or the nonsurgical wearing option is not aesthetically appealing [ 7 , 24 , 25 ]. It is therefore not surprising that at least one other manufacturer has presented a new nonsurgical alternative to implantable bone conduction devices recently [ 26 ]. If, as a result of these and similar new options, more hard-of hearing patients will actually use such devices, we believe that the practical relevance of these new devices is clearly given from the clinical point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Gawliczek et al reported and validated the use of the adhesive hearing device in 15 subjects with induced (i.e. occluded with earplugs) bilateral conductive hearing loss [10]. In our study, although two patients with unilateral aural atresia were satisfied with the device for an initial period of 1-2 months, they gradually found it bothersome to wear at 3 months; they wanted to use it only in noisy conditions as they had been used to hearing from only one side for so long.…”
Section: Discussionmentioning
confidence: 99%